2000
DOI: 10.4049/jimmunol.164.2.795
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mouse and Rabbit Eiκ Enhancers Indicates That Different Elements Within the Enhancer May Mediate Activation of Transcription and Recombination

Abstract: The intronic Ig κ-light chain enhancer (Eiκ) has been implicated in regulation of transcription and Vκ-Jκ recombination at the κ locus. To identify sequences within the Eiκ enhancer which are involved in control of recombination, we have made use of the finding that the Eiκ element from the rabbit b9 κ locus is capable of inducing rearrangement, but not transcription of κ genes in mouse lymphoid cells. We have therefore compared the binding of murine nuclear proteins to the mouse and rabbit Eiκ elements. DNase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…By analyzing the functional motifs within iE κ in vivo, we demonstrated that the κB site mutation had no apparent impact on κ rearrangement. The κB site is bound by NF-κB family members and was found to play an important role in activating κ rearrangement of recombination substrates in cell line transfection and transgenic studies ( 16 , 25 ). However, the findings that the impacts of κE1 and κE2 double mutation on κ rearrangement are very similar to the deletion of the entire iE κ rule out any important roles of other protein-binding motifs within iE κ , such as the NF-κB binding site, in activating κ rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…By analyzing the functional motifs within iE κ in vivo, we demonstrated that the κB site mutation had no apparent impact on κ rearrangement. The κB site is bound by NF-κB family members and was found to play an important role in activating κ rearrangement of recombination substrates in cell line transfection and transgenic studies ( 16 , 25 ). However, the findings that the impacts of κE1 and κE2 double mutation on κ rearrangement are very similar to the deletion of the entire iE κ rule out any important roles of other protein-binding motifs within iE κ , such as the NF-κB binding site, in activating κ rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear extracts of lymphoid cell lines and gel retardation experiments were performed as described previously (30). The mouse NF-B oligonucleotide used was 5Ј-GACAGAGGGGACTTTCCGAGAG-3Ј.…”
Section: Gel Retardation Assaysmentioning
confidence: 99%
“…Cell nuclei were prepared from RAG2 Ϫ/Ϫ CD19 ϩ pro-B cell precursors and S17 stromal cells as described previously (25). For restriction enzyme digest, 5 ϫ 10 6 nuclei were resuspended in 300 l of appropriate digestion buffer (New England Biolabs) and incubated with 50 U of restriction enzyme at 37°C.…”
Section: Restriction Endonuclease Accessibility Analysismentioning
confidence: 99%